Endophytic Bacteria as Biocontrol Agents of Xanthomonas campestris pv. manihotis on Cassava In Vitro - Purnawati, Arika (Proceeding International Conference on Global Resource Conservation, 2013)
Xanthomonas campestris pv. manihotis was important pathogen on cassava can cause plant die but the control still had not been taken seriously but now was study about endophytic bacteria as biocontrol agents for it. Endophytic bacteria are microbes which live symbiotically inside the plant tissue and without causing disease symptoms and had potential as biocontrol agents for it. The purpose of this research is to know the potential of endophytic bacteria that was isolated from cassava as biocontrol agents for it. The potential of  it was study using antagonism assay in vitro and characteristics of them based on the phenotypic characteristics were Gram reaction, hypersensitive reaction (HR) on tobacco leaf, anaerobic growth, catalase, carbohydrat hydrolyze, heat tolerance, NaCl tolerance. This assay used seed coating combination plate chlorofom method and used completely randomized design with 20 treatments of  isolates and each was repeated three times. The result of this research were 20 endophytic bacteria isolates and 4 isolates can inhibit of Xanthomonas campestris pv. manihotis growth in vitro.Keywords: endophytic bacteria,  biocontrol agents,  Xanthomonas campestris Pv. manihotis,